Interpreting as a stressful activity: Physiological measures of stress in simultaneous interpreting - Korpal, Paweł (My University, 2016)
The question of interpreter aptitude has been widely discussed in Interpreting Studies (e.g. Lambert 1991; Moser-Mercer 1994; Mackintosh 1999). Language command and cognitive skills have often been treated by interpreter trainers as the main determinants of an interpreter’s future success. However, in recent years, more and more attention from interpreting scholars has been devoted to psycho-affective factors, such as motivation, anxiety or stress resistance (e.g. Timarová and Ungoed-Thomas 2008; Rosiers et al. 2011; Bontempo and Napier 2011). This paper presents the results of a pilot study, the main objective of which was to examine whether the speed of speaker’s delivery influences the level of stress experienced by interpreting trainees during a simultaneous interpreting task. To this end, heart rate and blood pressure data were collected. The participants were asked to interpret two speeches from English into Polish. The author hypothesised that while interpreting a faster speech the participants would experience a higher level of stress than when they interpreted a slower speech. The hypothesis was corroborated only for heart rate values. No statistically significant differences were observed for either systolic or diastolic blood pressure. The study offers valuable insight into the question of stress experienced by interpreting trainees.
Keywords: psychological stress; simultaneous interpreting; heart rate; blood pressure; interpreter aptitude